After 9, 000 laparotomies for blunt trauma, resuscitation is becoming more balanced and time to intervention shorter: Evidence in action. Issue 3 (28th September 2022) - Douglas, Molly; Obaid, Omar; Castanon, Lourdes; Reina, Raul; Ditillo, Michael; Nelson, Adam; Bible, Letitia; Anand, Tanya; Gries, Lynn; Joseph, Bellal
Abstract : Resuscitation is becoming more balanced and time to emergency laparotomy shorter in blunt trauma patients, with significant improvements in mortality. PRBC:FFP ratio and time to emergency laparotomy should become markers of quality of trauma care. Abstract : BACKGROUND: Several advancements in hemorrhage control have been advocated for in the past decade, including balanced transfusions and earlier times to intervention. The aim of this study was to examine the effect of these advancements on outcomes of blunt trauma patients undergoing emergency laparotomy. METHODS: This is a 5-year (2013–2017) analysis of the Trauma Quality Improvement Program. Adult (18 years or older) blunt trauma patients with early (≤4 hours) packed red blood cell (PRBC) and fresh frozen plasma (FFP) transfusions and an emergency (≤4 hours) laparotomy for hemorrhage control were identified. Time-trend analysis of 24-hour mortality, PRBC/FFP ratio, and time to laparotomy was performed over the study period. The association between mortality and PRBC/FFP ratio, patient demographics, injury characteristics, transfusion volumes, and American College of Surgeons verification level was examined by hierarchical regression analysis adjusting for interyear variability. RESULTS: A total of 9, 773 blunt trauma patients with emergency laparotomy were identified. The mean ± SD age was 44 ± 18 years, 67.5% were male, and median Injury Severity Score was 34 (range, 24–43). The mean ± SD systolic blood pressure at presentation was 73 ± 28 mm Hg, and the median transfusion requirements were PRBC 9 (range, 5–17) and FFP 6 (range, 3–12). During the 5-year analysis, time to laparotomy decreased from 1.87 hours to 1.37 hours ( p < 0.001), PRBC/FFP ratio at 4 hours decreased from 1.93 to 1.71 ( p < 0.001), and 24-hour mortality decreased from 23.0% to 19.3% ( p = 0.014). On multivariate analysis, decreased PRBC/FFP ratio was independently associated with decreased 24-hour mortality (odds ratio, 0.88; p < 0.001) and in-hospital mortality (odds ratio, 0.89; p < 0.001). CONCLUSION: Resuscitation is becoming more balanced and time to emergency laparotomy shorter in blunt trauma patients, with a significant improvement in mortality. Future efforts should be directed toward incorporating transfusion practices and timely surgical interventions as markers of trauma center quality. LEVEL OF EVIDENCE: Therapeutic/care management, level III. Abstract :